2020
DOI: 10.1101/2020.11.06.20227215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal human coronavirus antibodies are boosted upon SARS-CoV-2 infection but not associated with protection

Abstract: SUMMARYSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread within the human population. Although SARS-CoV-2 is a novel coronavirus, most humans had been previously exposed to other antigenically distinct common seasonal human coronaviruses (hCoVs) before the COVID-19 pandemic. Here, we quantified levels of SARS-CoV-2-reactive antibodies and hCoV-reactive antibodies in serum samples collected from 204 humans before the COVID-19 pandemic. We then quantified pre-pandemic antibody level… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 20 publications
14
125
1
Order By: Relevance
“…While it is expected that IgM immunoglobulins are the first class detected following infection by SARS-CoV-2, as supported by a number of studies (37,39,40,111), others have paradoxically demonstrated IgG responses that precede the IgM response (38,(112)(113)(114)(115). This surprising discrepancy is likely related to cross-reactivity with pre-existing immunity to sCoVs (40,111,(116)(117)(118). Nevertheless, the largest body of evidence suggests that nearly all SARS-CoV-2 infected individuals begin to produce IgM, IgA, and then IgG by 1 to 2 weeks PSO ( Figure 1) (39,90,114,119,120).…”
Section: Dynamics Of the Antibody-mediated Immune Response To Sars-cov-2mentioning
confidence: 99%
See 4 more Smart Citations
“…While it is expected that IgM immunoglobulins are the first class detected following infection by SARS-CoV-2, as supported by a number of studies (37,39,40,111), others have paradoxically demonstrated IgG responses that precede the IgM response (38,(112)(113)(114)(115). This surprising discrepancy is likely related to cross-reactivity with pre-existing immunity to sCoVs (40,111,(116)(117)(118). Nevertheless, the largest body of evidence suggests that nearly all SARS-CoV-2 infected individuals begin to produce IgM, IgA, and then IgG by 1 to 2 weeks PSO ( Figure 1) (39,90,114,119,120).…”
Section: Dynamics Of the Antibody-mediated Immune Response To Sars-cov-2mentioning
confidence: 99%
“…Several serological studies have demonstrated cross-reactivity of SARS-CoV-2 S protein with SARS-CoV, MERS, and sCoVs (43,53,116,118,165,(173)(174)(175). The spike S2 domain is believed to be primarily responsible for this cross-recognition given its slightly higher level of sequence similarity than the other S domains (118).…”
Section: Cross-reactivity Of Sars-cov-2 Antibodies To Seasonal Covsmentioning
confidence: 99%
See 3 more Smart Citations